2016
DOI: 10.1002/slct.201600254
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Driven Epoxidation Is A Two-Stage Synergistic Process

Abstract: Lipases show high stability in lipophilic solvents and catalyze reactions at the water‐oil interfaces, which are of great industrial interest. One promising application of lipases is the production of epoxides from alkenes and hydrogen peroxide. So far, little attention has been given to uncover the reaction mechanism for this in detail at the molecular level. Here, we present structural and mutational analysis of a lipase from Penicillium camembertii that indicates a two‐stage synergistic mechanism for this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 20 publications
1
23
0
2
Order By: Relevance
“…We believe that the biological function of lipase could interfere with electron transfer between H 2 O 2 and TMB and, therefore, competes with TMB oxidation. As a result, the blue‐colored TMB ox product is not observed, and the reaction of lipase with H 2 O 2 could be the reason for this observation . Later, to test our hypothesis, we performed a postincubation study, in which the inhibitor was added 2 h after the reaction was set with lipase, MoS 2 2D‐nps, TMB, and H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the biological function of lipase could interfere with electron transfer between H 2 O 2 and TMB and, therefore, competes with TMB oxidation. As a result, the blue‐colored TMB ox product is not observed, and the reaction of lipase with H 2 O 2 could be the reason for this observation . Later, to test our hypothesis, we performed a postincubation study, in which the inhibitor was added 2 h after the reaction was set with lipase, MoS 2 2D‐nps, TMB, and H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Dentro de esta amplia gama de biocatalizadores, las lipasas son las enzimas que mayor atención han recibido debido a que han demostrado ser estables en diversos solventes orgánicos y soportar un amplio rango de temperaturas (Guncheva & Zhiryakova, 2011;Tang et al, 2016). Una de las lipasas con mayor potencial de aplicación en la industria oleoquímica es la lipasa B de Candida antarctica que se encuentra comercialmente disponible en forma inmovilizada dentro de una resina acrílica (Novozym 435) o inmovilizada en un gel de sílica (CALB-sílica) (Milchert, Malarczyk & Kłos, 2015), que ha sido empleada para catalizar la síntesis de un gran número de epóxidos como los derivados de ésteres de aceite de girasol, en donde se obtuvieron rendimientos del 99 % al llevarse a cabo la reacción en un sistema bifásico CH 2 Cl 2 /H 2 O a 30 °C (Schneider, Lara, Bitencourt, Nascimento & dos Santos-Nunes, 2009) o bien, en el caso de la epoxidación de ésteres de aceite de soya en donde la reacción fue llevada a cabo en presencia de tolueno como solvente a 55 °C para obtener productos con 98 % de rendimiento (Lu et al, 2010).…”
Section: Epoxidación Enzimáticaunclassified
“…In this study, the lipase PCL from Penicillieum camembertii was chosen, which has a strong specificity toward MAG and DAG but not TAG. Lipase PCL has been intensively investigated by us and others for various applications such as synthesis of conjugated linoleic acid glycerides (Hernández‐Martín, Hill, & Otero, ; Watanabe et al, ) or as catalyst for esterification and epoxidation reactions (Tang et al, ). Currently, no studies have specifically reported on the synthesis of α‐linolenic acid‐rich diacylglycerol using the lipase PCL.…”
Section: Introductionmentioning
confidence: 99%
“…Lipase PCL has been intensively investigated by us and others for various applications such as synthesis of conjugated linoleic acid glycerides (Hern andez-Martín, Hill, & Otero, 2009;Watanabe et al, 2002Watanabe et al, , 2004Watanabe et al, , 2005 or as catalyst for esterification and epoxidation reactions (Tang et al, 2016). Currently, no studies have specifically reported on the synthesis of a-linolenic acid-rich diacylglycerol using the lipase PCL.…”
mentioning
confidence: 99%